ANALISIS KESULITAN GURU DALAM MENGEMBANGKAN KETERAMPILAN BERPIKIR TINGKAT TINGGI PESERTA DIDIK PADA PEMBELAJARAN BIOLOGI SMA - Ermila Mahariyanti; Irwansah Irwansah (LPPM Institut Pendidikan Nusantara Global, 2021)
This study was aimed at analyzing the difficulties of teachers in developing students' higher order thinking skills in learning biology. The populations of this study were all teachers at SMAS IT Dhiaul Fikri and MA Darul Aminin. The samples of this study were all biology subject teachers at SMAS IT Dhiaul Fikri and MA Darul Aminin. Data collection was carried out by in-depth interviews with Biology teachers. The data analysis technique used is descriptive statistics. Descriptive statistics function to describe or provide an overview of the object under study with the aim of summarizing the data so that it is easy to understand through data samples or populations. The difficulties faced by teachers in developing students' higher-order thinking skills are: teachers find it difficult to cope with the different abilities of students, teachers are less able to determine appropriate learning methods and models, lack of understanding about developing higher order thinking skills, less able to adjust the questions with operational verbs contained in the learning indicators, and have not been able to cope with students who have different ways of showing their ability to think.